The influence of embryo stage on obstetric complications and perinatal outcomes following programmed compared to natural frozen-thawed embryo transfer cycles: a systematic review and meta-analysis - Zhao, Zhonghua; Chen, Yan; Deng, Hongxia; Huang, Lu; Lu, Danhua; Shen, Xiaoyang; Xu, Liangzhi (Frontiers in Endocrinology, 2023)
Objective To investigate the effect of embryo stage at the time of transfer on obstetric and perinatal outcomes in programmed frozen-thawed embryo transfer (FET) versus natural FET cycles. Design Systematic review and meta-analysis. Setting Not applicable. Patient(s) Women with programmed frozen-thawed embryo transfer (FET) and natural FET. Intervention(s) The PubMed, MEDLINE, and EMBASE databases and the Cochrane Central Register of Controlled Trials (CCRT) were searched from 1983 to October 2022. Twenty-three observational studies were included. Primary outcome measure The primary outcomes were hypertensive disorders of pregnancy (HDPs), gestational hypertension and preeclampsia (PE). The secondary outcomes were gestational diabetes mellitus (GDM), placenta previa, postpartum haemorrhage (PPH), placental abruption, preterm premature rupture of membranes (PPROM), large for gestational age (LGA), small for gestational age (SGA), macrosomia, and preterm delivery (PTD). Result(s) The risk of HDP (14 studies, odds ratio (OR) 2.17; 95% confidence interval (CI) 1.95-2.41; P<0.00001; I2 = 43%), gestational hypertension (11 studies, OR 1.38; 95% CI 1.15-1.66; P=0.0006; I2 = 19%), PE (12 studies, OR 2.09; 95% CI 1.88-2.32; P<0.00001; I2 = 0%), GDM (20 studies, OR 1.09; 95% CI 1.02-1.17; P=0.02; I2 = 8%), LGA (18 studies, OR 1.11; 95% CI 1.07-1.15; P<0.00001; I2 = 46%), macrosomia (12 studies, OR 1.15; 95% CI 1.07-1.24; P=0.0002; I2 = 31%), PTD (22 studies, OR 1.21; 95% CI 1.15-1.27; P<0.00001; I2 = 49%), placenta previa (17 studies, OR 1.2; 95% CI 1.02-1.41; P=0.03; I2 = 11%), PPROM (9 studies, OR 1.19; 95% CI 1.02-1.39; P=0.02; I2 = 40%), and PPH (12 studies, OR 2.27; 95% CI 2.02-2.55; P <0.00001; I2 = 55%) were increased in programmed FET cycles versus natural FET cycles with overall embryo transfer. Blastocyst transfer had a higher risk of HDP (6 studies, OR 2.48; 95% CI 2.12-2.91; P<0.00001; I2 = 39%), gestational hypertension (5 studies, OR 1.87; 95% CI 1.27-2.75; P=0.002; I2 = 25%), PE (6 studies, OR 2.23; 95% CI 1.93-2.56; P<0.00001; I2 = 0%), GDM (10 studies, OR 1.13; 95% CI 1.04-1.23; P=0.005; I2 = 39%), LGA (6 studies, OR 1.14; 95% CI 1.07-1.21; P<0.0001; I2 = 9%), macrosomia (4 studies, OR 1.15; 95% CI 1.05-1.26; P<0.002; I2 = 68%), PTD (9 studies, OR 1.43; 95% CI 1.31-1.57; P<0.00001; I2 = 22%), PPH (6 studies, OR 1.92; 95% CI 1.46-2.51; P<0.00001; I2 = 55%), and PPROM (4 studies, OR 1.45; 95% CI 1.14-1.83; P=0.002; I2 = 46%) in programmed FET cycles than in natural FET cycles. Cleavage-stage embryo transfers revealed no difference in HDPs (1 study, OR 0.81; 95% CI 0.32-2.02; P=0.65; I2 not applicable), gestational hypertension (2 studies, OR 0.85; 95% CI 0.48-1.51; P=0.59; I2 = 0%), PE (1 study, OR 1.19; 95% CI 0.58-2.42; P=0.64; I2not applicable), GDM (3 study, OR 0.79; 95% CI 0.52-1.20; P=0.27; I2 = 21%), LGA (1 study, OR 1.15; 95% CI 0.62-2.11; P=0.66; I2not applicable), macrosomia (1 study, OR 1.22; 95% CI 0.54-2.77; P=0.64; I2 not applicable), PTD (2 studies, OR 1.05; 95% CI 0.74-1.49; P=0.79; I2 = 0%), PPH (1 study, OR 1.49; 95% CI 0.85-2.62; P=0.17; I2not applicable), or PPROM (2 studies, OR 0.74; 95% CI 0.46-1.21; P=0.23; I2 = 0%) between programmed FET cycles and natural FET cycles. Conclusion(s) The risks of HDPs, gestational hypertension, PE, GDM, LGA, macrosomia, SGA, PTD, placenta previa, PPROM, and PPH were increased in programmed FET cycles versus natural FET cycles with overall embryo transfer and blastocyst transfer, but the risks were not clear for cleavage-stage embryo transfer.